A novel approach for the co-delivery of 5-fluorouracil and everolimus for breast cancer combination therapy: stimuli-responsive chitosan hydrogel embedded with mesoporous silica nanoparticles - Arvejeh, Pooria Mohammadi; Chermahini, Fatemeh Amini; Marincola, Francesco; Taheri, Fatemeh; Mirzaei, Seyed Abbas; Alizadeh, Akram; Deris, Fatemeh; Jafari, Raziyeh; Amiri, Niloufar; Soltani, Amin; Bijad, Elham; Dehkordi, Ebrahim Soleiman; et al. (Journal of translational medicine, 2025)
Background Breast cancer remains one of the leading causes of death among women globally, with traditional therapies often limited by challenges such as drug resistance and significant side effects. Combination therapies, coupled with nanotechnology-based co-delivery systems, offer enhanced efficacy by targeting multiple pathways in cancer progression. In this study, we developed an injectable, stimuli-responsive nanosystem using a chitosan hydrogel embedded with mesoporous silica nanoparticles for the co-administration of 5-fluorouracil and everolimus. This approach aims to optimize controlled drug release, enhance the synergistic anticancer effect, and overcome challenges associated with co-loading different therapeutic agents. Methods Various techniques were employed to characterize the nanoparticles and the hydrogel. Cell uptake, apoptosis, and proliferation of 4T1 breast cancer cells were evaluated by flow cytometry and Resazurin assay, respectively. The Balb/C mice model of breast cancer, which received the therapeutical nanoplatforms subcutaneously near the tumoral region was used to examine tumor size and lung metastases. Results The results revealed that the nanoparticles had a suitable loading capacity and high cellular uptake. The drug release was pH-sensitive and synergistic. By incorporating nanoparticles into the hydrogel, the cell death rate and apoptosis of 4T1 breast cancer cells increased significantly, due to the synergistic effects of co-delivered drugs. Additionally, the combination treatment groups showed a significant reduction in tumor size and lung metastasis compared to the monotherapy and control groups. Conclusions These findings underscore the potential of the nanocomposite used to develop a novel co-delivery system to enhance therapeutic outcomes, reduce side effects, and provide a promising new strategy for future cancer treatments.